A re-assessment of common theoretical approaches to explain gender differences in continuing training participation - Dieckhoff, Martina [Verfasser]; Steiber, Nadia [Verfasser] (My University, 2011)
"It is often argued that gender differences in access to continuing training are a central cause of persisting gender inequalities in occupational attainment. Yet existing empirical work has presented rather mixed evidence regarding a potential sex gap in training participation. In this article, we carry out an empirical test of the central theoretical models commonly used to explain gender differences in continuing training participation. Using the European Social Survey, we find that male employees are more likely to train than their female colleagues, controlling for worker, firm and job characteristics, with some tentative evidence for differences across countries. Common theoretical approaches to understanding gender differences in continuing skill investment to some degree explain men's training incidence, while they largely fail to predict that of women." (Autorenreferat, BIBB-Doku)
Keywords: S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; G 2.4.5 Gender Mainstreaming; I 2.2 Europa; Bildungschancengleichheit; Weiterbildungsbeteiligung; Gender Mainstreaming; Empirische Untersuchung; Europa